I have to prove that:
\sum_{k=0}^{n} {{m+k} \choose{m}} = { m+n+1 \choose m+1 }
I tried to open up the right side with Pascal's definition that:
{ n \choose k} = {n-1 \choose {k}} + {n-1 \choose {k-1}}
Here is what I came up with, and I am sure it is wrong because it does not equal the left side:
{m+n+1 \choose m+1} = {m+n \choose m+1} + {m+n \choose m} = ... ={m+n \choose m+1} + {m+n-1 \choose m} + {m+n-2 \choose m-1} + ... + {m \choose m+1} = \sum_{k=0}^{n} {m+k \choose m+k-n+1 }
Which, again, probably is wrong because it is not equal \sum_{k=0}^{n} { m+k \choose m}.
Any help is appreciated
Answer
Here is a purely combinatorial proof:
Consider picking m+1 numbers out of \{1,2,...,m, \color{ #009900}{m + 1}, \color{ #009900}{m + 1} + 1,...,\color{ #009900}{m + 1} + (n - 1),\color{ #009900}{m + 1}+n\}.
The right hand side of your equation is clearly equal to the number of ways of doing this.
Now for any given choice of m+1 numbers, the highest number chosen must be some k with \color{ #009900}{m + 1} \leq k \leq \color{ #009900}{m + 1}+n. In each of these cases, we must select the remaining m numbers to be chosen from the k-1 numbers smaller than k.
For k = m +1, must pick m numbers to the left of m + 1, out of \{\color{ #0073CF}{1, 2, ..., m}, m+1\}.
Since there are \color{#0073CF}{m} such numbers, so \color{#0073CF}{m} possible choices for m.
Thus the total number of choices for m numbers = \binom{\color{#0073CF}{m}}{m}.
For k = m +2, must pick m numbers to the left of m + 2, out of \{\color{ #0073CF}{1, 2, ..., m, m +1}, m+2\}.
Since there are \color{#0073CF}{m + 1} such numbers, so \color{#0073CF}{m + 1} possible choices for m.
Thus the total number of choices for m numbers = \binom{\color{#0073CF}{m + 1}}{m}.
...
For k = m + 1 + n, must pick m numbers to the left of m + 1 + n, out of \{\color{ #0073CF}{1, 2, ..., m, m +1, ..., m + n}, m+ n + 1\}.
Since there are \color{#0073CF}{m + n} such numbers, so \color{#0073CF}{m + n} possible choices for m.
Thus the total number of choices for m numbers = \binom{\color{#0073CF}{m + n}}{m}.
Summing up the number of ways of doing this for k=m+1,...,m+n+1 yields the LHS of your equation.
No comments:
Post a Comment